2005
DOI: 10.2174/1568008054863754
|View full text |Cite
|
Sign up to set email alerts
|

Caspases as Drug Targets in Ischemic Organ Injury

Abstract: Caspases are intracellular cysteine proteases that mediate cell death and inflammation. Caspase-3 is a major mediator of both apoptotic and necrotic cell death. Caspase-1 mediates inflammation though the activation of the cytokines interleukin-1beta (IL-1beta) and interleukin-18 (IL-18). Increases in both caspase-1 and -3 have been described in ischemic injury to various organs including brain, heart and kidney. Both pharmacological inhibitors and genetic approaches have been used to inhibit caspases in vivo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 96 publications
(160 reference statements)
1
55
1
3
Order By: Relevance
“…IL-18 is specific to the renal tubules and is known to be up-regulated in response to ischemia reperfusion injury. 30 However, initial creatinine elevations after ischemic injury often do not occur until 24-48 hours after an insult (68.4% of our cohort developed AKI on or after day 2). 31 Thus, creatinine kinetics supply ample time for urinary IL-18 concentrations to dissipate, and this time lag may explain why other markers displayed more robust results.…”
Section: Discussionmentioning
confidence: 74%
“…IL-18 is specific to the renal tubules and is known to be up-regulated in response to ischemia reperfusion injury. 30 However, initial creatinine elevations after ischemic injury often do not occur until 24-48 hours after an insult (68.4% of our cohort developed AKI on or after day 2). 31 Thus, creatinine kinetics supply ample time for urinary IL-18 concentrations to dissipate, and this time lag may explain why other markers displayed more robust results.…”
Section: Discussionmentioning
confidence: 74%
“…104 -106 In vivo caspase inhibitors protect against ischemic injury in brain, heart, and kidney. 63 The pan caspase inhibitor zVAD prevents the impairment of renal function at an early time point (24 h) when administered at the time of reperfusion. 62 It is much less effective when administered 2 h later.…”
Section: Nephrotoxins Illustrate Intracellular Death Pathwaysmentioning
confidence: 99%
“…Ischemic injury can initiate a cascade of events that results in inflammation and cell death by apoptosis and necrosis (Faubel, Edelstein, 2005). Apoptosis is a type of cell death that occurs as a cascade of cellular machinery.…”
Section: Discussionmentioning
confidence: 99%
“…This well-established cold storage medium has also been used for preserving segments of peripheral nerves, but it was shown that peripheral nerve segments stored in UWS over a long period of time (≥3 weeks) resulted in nerves with few viable SCs that were essentially acellular conduits (Levi et al, 1994). Ischemic injury may be partly responsible for the decrease in viable SCs, because it can initiate a cascade of events that results in cell death by apoptosis and necrosis (Faubel, Edelstein, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation